2010
DOI: 10.1111/j.1365-2486.2009.02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Faster returns on ‘leaf economics’ and different biogeochemical niche in invasive compared with native plant species

Abstract: Plant-invasive success is one of the most important current global changes in the biosphere. To understand which factors explain such success, we compared the foliar traits of 41 native and 47 alien-invasive plant species in Oahu Island (Hawaii), a location with a highly endemic flora that has evolved in isolation and is currently vulnerable to invasions by exotic plant species. Foliar traits, which in most cases presented significant phylogenetic signal, i.e. closely related species tended to resemble each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
155
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(172 citation statements)
references
References 46 publications
13
155
1
3
Order By: Relevance
“…The trend of higher leaf-nutrient load (especially N, P and K) in exotic vines M. unguis-cati and P. suberosa (Table 3) is linked to the preference of invasive plant species for disturbed habitats commonly associated with high pulses of nutrient input (Davis et al 2000). As in our study, Penuelas et al (2010) found that several invasive species had enhanced capacities in terms of productivity and nutrient capture both of macro-(N, P, K) and micro elements (Fe, Ni, Cu and Zn) and suggested that potential increases in soil nutrient availability might favour further success of invasive plants.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…The trend of higher leaf-nutrient load (especially N, P and K) in exotic vines M. unguis-cati and P. suberosa (Table 3) is linked to the preference of invasive plant species for disturbed habitats commonly associated with high pulses of nutrient input (Davis et al 2000). As in our study, Penuelas et al (2010) found that several invasive species had enhanced capacities in terms of productivity and nutrient capture both of macro-(N, P, K) and micro elements (Fe, Ni, Cu and Zn) and suggested that potential increases in soil nutrient availability might favour further success of invasive plants.…”
Section: Discussionsupporting
confidence: 60%
“…M. unguis-cati leaves also had higher concentrations of potentially toxic ions (Al, Cd, Co and Cu) than the concentrations present in leaves of non-invasive species (Table 3), indicating that M. unguis-cati may more readily take up metal contaminants from the soil than do native species. Penuelas et al (2010), in a general survey of leaf economics of invasives and biogeochemical niche, alluded to the relatively higher abundance of these potentially toxic trace elements in many invasive plant organs and suggested that the cycling of these elements could be accelerated in invasive alien-dominated ecosystems. However, the influence of M. unguis-cati in altering the soil's biogeochemical cycle appeared not to be as dramatic as that of Lantana camara, known to decrease the concentrations of a greater number of heavy and/or toxic metals such as Fe, Cu, Mn and S (see Osunkoya and Perrett 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations